$δ(τ_{1},τ_{2})$-Continuous Functions (European Journal of Pure and Applied Mathematics, 2024)
This paper introduces a new class of functions called $δ(τ_{1},τ_{2})$-continuous functions. Several characterizations of $δ(τ_{1},τ_{2})$-continuous functions are investigated. The relationships between $δ(τ_{1},τ_{2})$-continuity and the other types of $δ(τ_{1},τ_{2})$-continuity are also discussed.
Keywords: $δ(τ_{1},τ_{2})$-open set; $δ(τ_{1},τ_{2})$-continuous function; almost $δ(τ_{1},τ_{2})$-continuous function; weakly $δ(τ_{1},τ_{2})$-continuous function